Symmetrical components for power systems engineering - Blackburn, J. Lewis (Electrical engineering and electronics, 1993)
Emphasizing a practical conception of system unbalances, basic circuits, and calculations, this essential reference/text presents the foundations of symmetrical components with a review of per unit (percent), phasors, and polarity--keeping the mathematics as simple as possible throughout